2022
DOI: 10.1039/d2cp02293a
|View full text |Cite
|
Sign up to set email alerts
|

General cluster sorption isotherm: surface area determination

Abstract: The recently published General Cluster Sorption Isotherm is modified by separating forces lateral and vertical directed to the surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…An isotherm is the main data source for surface area estimation. Some researchers have suggested that the pressure range of BET analysis should obey four criteria; some researchers have modified the traditional BET equation to obtain a more reasonable surface area; and some others have developed new isotherm models to describe the adsorption process and then derive the surface area, e.g., zeta adsorption isotherms, , cluster sorption isotherms, and the isotherm model based on Polanyi’s theory. , In addition to utilizing isotherms, some other methods can also determine the surface area, such as using electron microscopy , and mathematically calculating according to the crystal structure. , Most of these studies have concluded that the traditional BET method will overestimate the surface area. ,,,, …”
Section: Introductionmentioning
confidence: 99%
“…An isotherm is the main data source for surface area estimation. Some researchers have suggested that the pressure range of BET analysis should obey four criteria; some researchers have modified the traditional BET equation to obtain a more reasonable surface area; and some others have developed new isotherm models to describe the adsorption process and then derive the surface area, e.g., zeta adsorption isotherms, , cluster sorption isotherms, and the isotherm model based on Polanyi’s theory. , In addition to utilizing isotherms, some other methods can also determine the surface area, such as using electron microscopy , and mathematically calculating according to the crystal structure. , Most of these studies have concluded that the traditional BET method will overestimate the surface area. ,,,, …”
Section: Introductionmentioning
confidence: 99%